Ugly : The True Story of a LoveLess Childhood - Briscoe, Constance, 1957- (London Hodder & Stoughton, 2006)
Constance's mother systematically abused her daughter, both physically and emotionally, throughout her childhood. Regularly beaten and starved, the girl was so desperate she took herself off to Social Services and tried to get taken into care. This book presents her heartrending - and ultimately triumphant - story.
Include Epilogue
Keywords: Abused children -- Briscoe, Constance, 1957- -- Abandoned children